The effect of nanocoatings enriched with essential oils on ‘Rocha’ pear long storage - Gago, Custódia (2020)
The effect of coating 'Rocha' pears with alginate-based nanoemulsions enriched with lemongrass essential oil (LG) or citral (Cit) was investigated. Fruit were treated with the nanoemulsions: sodium alginate 2% (w/w) + citral 1% (w/w) (Cit1%); sodium alginate 2% (w/w) + citral 2% (w/w) (Cit2%); sodium alginate 2% (w/w) + lemongrass 1.25% (w/w) (LG1.25%); sodium alginate 2% (w/w) + lemongrass 2.5% (w/w) (LG2.5%). Then, fruit were stored at 0 °C and at 95% relative humidity, for six months. Fruit samples were taken after two, four and six months, and then placed at 22 °C. Upon removal and after 7 d shelf-life, fruit were evaluated for colour CIE (L*, h◦), firmness, soluble solids content (SSC), titratable acidity (TA), weight loss, electrolytic leakage, microbial growth, symptoms of superficial scald and internal browning. All nanoemulsions had droplets in the nano range <500 nm, showed uniformity of particle size and stable dispersion. Cit-nanoemulsions had lower droplet size and higher stability than LG. No nanoemulsion showed cytotoxicity. Coatings reduced fruit colour evolution and preserved better firmness than control. After shelf-life, better firmness was found in LG-coated fruit. Coatings did not affect SSC and TA. Microbial growth was below the safety limits in all treatments. Fruit treated with LG-nanoemulsions did not show scald symptoms and panelists preferred LG1.25% coated fruit. Cit2% treated fruit showed the highest scald and internal browning symptoms, while LG1.25% did not show any disorders. This study suggests that LG-nanocoatings have the potential for preserving the quality of 'Rocha' pear.